Impulse response correction enables high-resolution clinical hand-held optoacoustics - Juestel, Dominik; Chowdhury, Kaushik Basak; Bader, Maximilian; Dehner, Christoph; Ntziachristos, Vasilis (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2021)
The total impulse response of a clinical optoacoustic system is characterized by combining experimentally acquired signals with a numerical model of the spatial impulse response, resulting in high-resolution images in clinical applications.
CRIS-Team Scopus Importer:2023-03-08